Brexanolone, a GABAA Modulator, in the Treatment of Postpartum Depression in Adults: A Comprehensive Review - Edinoff, Amber N.; Odisho, Amira S.; Lewis, Kendall; Kaskas, Amir; Hunt, Grace; Cornett, Elyse M.; Kaye, Alan D.; Kaye, Adam; Morgan, John; Barrilleaux, P. Scott; Lewis, David; Viswanath, Omar; et al. (Frontiers in Psychiatry, 2021)
Postpartum depression (PPD) is one of the three major categories on the spectrum of postpartum psychiatric syndromes. Postpartum psychiatric syndromes are classified as either postpartum blues, postpartum depression, or postpartum psychosis. Postpartum depression is important to recognize clinically because of the effect it can have on the mother-child bond. The neurosteroid allopregnanolone, a progesterone derivative, is important for its role in positively modulating GABAA receptors. GABA-mediated signaling has been previously implicated in major depressive disorder. Allopregnanolone-mediated signaling has been identified as an important therapeutic target. Treatment with an allopregnanolone-analog, brexanolone, has been shown to improve depression scores in trials for the treatment of PPD. Brexanolone is a positive allosteric modulator of GABAA and is the first drug approved by the FDA to treat postpartum depression. Brexanolone enhances the inhibitory effects of GABAA, restores dysfunctional GABAA transmembrane channels, and mimics a naturally produced progesterone metabolite that fluctuates during pregnancy and postpartum. One open-label study and two phase two studies have some significant reduction in HAM-D scores after treatment and that the effect was still there 30 days post-treatment. Per the data reported, intravenous infusion of brexanolone could be efficacious and safe for the treatment of women suffering from postpartum depression.